Youth ministry as a public practical theology: A South African evangelical perspective - Aziz, Garth (HTS teologiese studies, 2022)
Youth ministry as a sub-discipline of practical theology has traditionally always had an ecclesial focus. The focus was often based on the practices of proselytisation and discipleship, a sort of ‘reach and teach’ model whereby Christian believers would do the ‘reaching and teaching’ of the ‘lost’ youth. This is most true in an evangelical context and is further undergirded by a Western concept of personal salvation nearly devoid of any communal responsibilities and context. The traditional model, therefore, in evangelical churches was reaching the ‘lost’ with the Gospel of Jesus Christ, with the aim of personal salvation for the individual who would eventually become a member of the faith community through a discipleship programme. Thus, the beginning and end of the entire process were the focus on personal salvation devoid of any contextual consideration. Youth ministry as practical theology must move into the area of public theology to engage the practices inherited from the western model by engaging with the public (youths) as public theologians (those who influence the theologies of the youth), and the public faiths and spiritualities (the expression of the youth’s theologies) to be relevant to the majority and developing world.Contribution: In this study, the author suggests that this ‘reach and teach’ paradigm with an ecclesial focus in the context of the majority and developing world is no longer suitable to meet the needs of youth. In addition, the author recommends a more appropriate framework with youth ministry as public practical theology for consideration.